2013
DOI: 10.11648/j.ab.20130102.11
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Cold on Cytochromes Р450 1А in the Rat Lungs Versus Liver

Abstract: During hypothermia, most cellular processes are inhibited, including expression of numerous genes. A small number of special genes are activated, which code for proteins participating in cold acclimation of the cell. We previously uncovered a paradoxical phenomenon: cytochrome P450 subfamily enzymes (CYP1A) in rat liver are not inhibited but activated by systemic cooling. In the present study, we have investigated the influence of cold exposure on the activity and expression level of the CYP1A proteins in a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Some functional analyses have shown that cytochrome P450 genes closely related to the fat metabolism (e.g., CYP7A1 and CYP1A1) play important roles in cold stress ( Chen et al, 2012 ). Interestingly, exposure to low temperatures inhibits gene expression and most cellular processes in rats, with the exception of cytochrome P450 enzymes (CYP1A) in liver, which are instead activated by cold ( Perepechaeva and Grishanova, 2013 ). Here, detoxification-associated genes were upregulated at 28°C or 10°C in the cold-tolerant shrimp (LV-T) as compared to the common shrimp (LV-C; Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some functional analyses have shown that cytochrome P450 genes closely related to the fat metabolism (e.g., CYP7A1 and CYP1A1) play important roles in cold stress ( Chen et al, 2012 ). Interestingly, exposure to low temperatures inhibits gene expression and most cellular processes in rats, with the exception of cytochrome P450 enzymes (CYP1A) in liver, which are instead activated by cold ( Perepechaeva and Grishanova, 2013 ). Here, detoxification-associated genes were upregulated at 28°C or 10°C in the cold-tolerant shrimp (LV-T) as compared to the common shrimp (LV-C; Table 1 ).…”
Section: Discussionmentioning
confidence: 99%